1998
DOI: 10.1021/jo971357x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Electronic Structures of Heteroaromatic Oligomers:  Model Compounds of Polymers with Quantum-Well Structures

Abstract: Conformational preferences of 2,2′-bithiophene, 2-(2-thienyl)pyrrole, and N-methyl-2-(2-thienyl)pyrrole have been investigated by means of computational methods. Calculations were performed at the ab initio HF/6-31G(d) and MP2/6-31G(d) levels and, additionally, with the density functional B3-LYP/6-31G(d). The results indicate that 2-(2-thienyl)pyrrole behaves similarly to the 2,2′bithiophene. Thus, two minimum energy conformations were found for each compound, which correspond to anti-gauche and syn-gauche. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 42 publications
9
45
0
3
Order By: Relevance
“…These results are fully consistent with the rotational profile predicted by quantum mechanical methods for the inter-ring dihedral angle, [45][46][47][48][49] which indicated that the syn conformation is severely destabilized when adjacent substituted thiophene rings show a head-head linkage but energetically accessible for head-tail and tail-tail linkages. From an electronic point of view, the distortion of the interring dihedral angle from anti to syn destroys the extent of the π -conjugation along the polymer chain.…”
Section: Molecular Dynamics Simulationssupporting
confidence: 86%
“…These results are fully consistent with the rotational profile predicted by quantum mechanical methods for the inter-ring dihedral angle, [45][46][47][48][49] which indicated that the syn conformation is severely destabilized when adjacent substituted thiophene rings show a head-head linkage but energetically accessible for head-tail and tail-tail linkages. From an electronic point of view, the distortion of the interring dihedral angle from anti to syn destroys the extent of the π -conjugation along the polymer chain.…”
Section: Molecular Dynamics Simulationssupporting
confidence: 86%
“…La geometría y el perfil rotacional de estos compuestos fueron analizados mediante cálculos ab initio de mecánica c u á n t i c a [12] , obteniendo resultados que concuerdan perfectamente con los datos experimentales disponibles. Más recientemente, extendimos el estudio a oligómeros de tiofeno de mayor tamaño [13,14] . Como ejemplo de este tipo de estudios, en la Figura 3 se representa el perfil rotacional teórico del 2,2'-bitiofeno, obtenido a nivel de cálculo B3PW91/6-31+G(d,p) [15] , donde se puede apreciar la presencia de dos conformaciones de energía mínima [16] .…”
Section: Modelización Molecular Modelización Molecular Modelización Munclassified
“…Desde el punto de vista teórico, se puede modelizar separadamente la cadena polimérica neutra y la eléctricamente cargada, para después analizar las diferencias estructurales entre ambas. De esta manera, pudimos comprobar que la estructura electrónica del 2,2'-bitiofeno y la del 2,2',5',2"-tertiofeno son aromáticas, mientras que sus respectivos dicationes presentan una distribución de electrones con carácter quinoideo [13,20] . Posteriormente, con la intención de acercarnos más a las características reales del politiofeno, utilizamos modelos de mayor tamaño que contenían hasta 13 anillos de tiofeno [21] .…”
Section: Modelización Molecular Modelización Molecular Modelización Munclassified
“…Por ejemplo, se puede determinar los modos normales de vibración (frecuencia e intensidad) característicos de los espectroscopía i.r. [73][74][75][76] , las constantes de acoplamiento de E.P.R [77,78] , etc……”
Section: Análisis De Parámetrunclassified